Validação de conteúdo do instrumento para consulta de enfermagem na visita domiciliar às pessoas com lesão medular: um enfoque no autocuidado - Coura, Alexsandro Silva (2013)
This study aimed to validate the contents of an Instrument for Nursing Consultation in the Home Visit of people with Spinal Cord Injury (INCEVDOP-LM), based on the Self-Care Deficit Theory. The methodological development study was conducted with spinal cord injured (SCI) people ascribed in the Family Health Units the city of Natal/RN/Brazil, and with the nurses of these institutions. The study was conducted from Januray 2012 to January 2013 in two phases: the first aimed to identify the need for self-care of persons with SCI, and the second to develop and validate the INCEVDOP-LM. The first phase consisted of a census study of people with SCI living in Natal/RN. In the second phase, a non-probabilistic convencience sample of subjects was selected to form two groups: First stage - Group 1 of the first stage was comprised by 73 adults with SCI diagnosed with paraplegia or tetraplegia, with cognitive function preserved and that were registered to some family health unit; Group 2 of the Second phase was composed of six experts that were nurses with doctoral formation, scientific experience in the area of technology development or assistance to persons with SCI, and with publications in periodicals Qualis A2. Data collection of the first phase was conducted through home visits of people with SCI that responded three instruments: Questionnaire I (comprised of demographic and socioeconomic variables), The Competency Rating Scale for Self-care (ASA) and the Barthel Index (an instrument for evaluation of functional capacity). The research for the second phase was conducted in two stages: I-construction of the INCEVDOP LM; II-validation of the INCEVDOP-LM. The instrument and an evaluation form were forwarded to the experts for the validation. The correlations between the responses were analyzed by the Kappa test, with accepting values of>0.75. The evaluation criteria were: organization, clarity, simplicity, readability, appropriateness of vocabulary, objectivity, accuracy, reliability and suitability and the positive responses with frequency values of≥90% were considered excellent. The chi-square test was used to investigate the differences between proportions. The study attended to the principles of Human Rights CNS Resolution 196/96. Results were reported by means of four articles derived from the study. The findings indicate that the items that showed disagreement among experts (k=0.02) were diagnoses, interventions and evaluation of the nursing features pertaining to the domains of Nutrition, Hygiene, Elimination, Physical, Social and Psychological, and of the Ability to perform work activities feature. Agreement among the experts were reported for the other items, with kappa ranging from 0.72 to 1. After removing items with disagreement, all criteria achieved excellent rates and no significant differences were observed between the proportions of responses of evaluation of experts (p>0.05). We conclude that the instrument shows validity to serve as a guide for nurses to conduct a systematic consultation during the home visit to people with spinal cord injury, with emphasis on self-care. The instrument must go through other levels of validation when applied in the clinical setting